2002
DOI: 10.1046/j.1365-313x.2002.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sterol biosynthesis genes in embryonic development of Arabidopsis

Abstract: SummaryThe sterol biosynthesis pathway of Arabidopsis produces a large set of structurally related phytosterols including sitosterol and campesterol, the latter being the precursor of the brassinosteroids (BRs). While BRs are implicated as phytohormones in post-embryonic growth, the functions of other types of steroid molecules are not clear. Characterization of the fackel (fk) mutants provided the ®rst hint that sterols play a role in plant embryogenesis. FK encodes a sterol C-14 reductase that acts upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 42 publications
9
131
0
1
Order By: Relevance
“…4; Supplemental Figs. S7 and S8) were very similar to those of the fk, hyd1, and smt1/cph mutants (Diener et al, 2000;Jang et al, 2000;Schrick et al, 2000Schrick et al, , 2002Souter et al, 2002). Second, a previous study showed that loss of function of both Arabidopsis CSDs, which are directly downstream of SMO2 (Supplemental Fig.…”
Section: Smo2s Are Essential For Embryogenesissupporting
confidence: 64%
See 4 more Smart Citations
“…4; Supplemental Figs. S7 and S8) were very similar to those of the fk, hyd1, and smt1/cph mutants (Diener et al, 2000;Jang et al, 2000;Schrick et al, 2000Schrick et al, , 2002Souter et al, 2002). Second, a previous study showed that loss of function of both Arabidopsis CSDs, which are directly downstream of SMO2 (Supplemental Fig.…”
Section: Smo2s Are Essential For Embryogenesissupporting
confidence: 64%
“…4, B-H). These arrested embryos showed patterning defects similar to those of the fk, hyd1, and smt1/cph mutants (Diener et al, 2000;Jang et al, 2000;Schrick et al, 2000Schrick et al, , 2002Souter et al, 2002;Willemsen et al, 2003) and did not develop the characteristic heart shape (Supplemental Fig. S7A).…”
Section: -E)mentioning
confidence: 68%
See 3 more Smart Citations